Paclitaxel resistance development is associated with biphasic changes in reactive oxygen species, mitochondrial membrane potential and autophagy with elevated energy production capacity in lung cancer cells: A chronological study - Satabdi Datta; Diptiman Choudhury; Amlan Das; Dipanwita Das Mukherjee; Nabanita Das; Sib Sankar Roy; Gopal Chakrabarti (Tumor Biology)
Paclitaxel (Tx) is one of the first-line chemotherapeutic drugs used against lung cancer, but acquired resistance to this drug is a major challenge against successful chemotherapy. In this work, we have focused on the chronological changes of various cellular parameters and associated effect on Tx (10 nM) resistance development in A549 cell line. It was observed, at initial stage, the cell death percentage due to drug treatment had increased up to 20 days, and thereafter, it started declining and became completely resistant by 40 days. Expressions of βIII tubulin and drug efflux pumps also increased over the period of resistance development. Changes in cellular autophagy and reactive oxygen species generation showed a biphasic pattern and increased gradually over the course of upto 20 days, thereafter declined gradually; however, their levels remained higher than untreated cells when resistance was acquired. Increase in extracellular acidification rates and oxygen consumption rates was found to be directly correlated with acquisition of resistance. The depolarisation of mitochondrial membrane potential was also biphasic; first, it increased with increase of cell death up to 20 days, thereafter, it gradually decreased to normal level along with resistance development. Increase in activity of catalase, glutathione peroxidase and glutathione content over these periods may attribute in bringing down the reactive oxygen species levels and normalisation of mitochondrial membrane potential in spite of comparatively higher reactive oxygen species production by the Tx-resistant cells.